Non hodgkin’s lymphoma misdiagnosed as tuberculosis: A case report (Indian Journal of Case Reports, 2019)
Non-Hodgkin’s Lymphoma is a heterogeneous group of malignancies characterized by an abnormal clonal proliferation of T-cells, B-cells or both. Sometimes, tuberculosis and lymphoma presentation can share common symptoms and features. A 37-year-old male patient was admitted in the hospital with complains of shortness of breath associated with cough, loss of appetite, generalized weakness and weight loss since two months. There were no palpable peripheral lymph nodes present anywhere in the body. The patient had no personal or family history of tuberculosis. The chest X-ray showed bilateral mild pleural effusion with confluent radio opacities in both lung fields. Pleural fluid biochemistry showed increased Adenosine deaminase level with increased protein and low sugar. Antitubercular drugs were started after initial diagnosis of tuberculosis. After non improvement in symptoms fine needle aspiration cytology (FNAC) was done from spleen which showed finding suggestive of non- hodgkins lymphoma.